LncRNA DDX11-AS1 promotes cell growth, migration and invasion through regulating epithelial-mesenchymal transition in breast cancer: LncRNA DDX11-AS1 in breast cancer - Xi, Xun; Yang, Fulan; Ding, Zhenluo; Zhuang, Haoxiang; Yuan, Huozhong (Cellular and Molecular Biology, 2024)
This study aimed to investigate the expression of long non-coding ribonucleic acid (lncRNA) DDX11 antisense RNA 1 (DDX11-AS1) in breast cancer (BC) tissues and cells and investigate its biological function and potential molecular mechanism through in vitro experiments. Tissue specimens were obtained from 44 BC patients. TRIzol method was used to extract RNAs from the tissues. The relative expression of DDX11-AS1 in BC tissues and the expression of DDX11-AS1 in BC cells were detected via quantitative reverse transcription-polymerase chain reaction (qRT-PCR). The effect of DDX11-AS1 on the proliferation ability of BC cells was detected via cell counting kit-8 (CCK-8) assay. Flow cytometry was adopted to study the effect of DDX11-AS1 on the distribution of BC cell cycle. Transwell assays were performed to analyze the effects of DDX11-AS1 on the migration and invasion abilities of BC cells. Finally, after interfering with the expression of DDX11-AS1 in BC cells, changes in the expressions of molecular markers for epithelial-mesenchymal transition (EMT) were detected via Western blotting. According to the results of qRT-PCR, the expression of DDX11-AS1 was up-regulated in 38 out of 44 cases of BC tissues compared with that in the para-carcinoma tissues, and the expression of DDX11-AS1 in BC cells was up-regulated as well. After interference with the expression of DDX11-AS1 in BC cells, it was found via CCK-8 assay that the proliferation ability of BC cells was restrained, flow cytometry results showed that the BC cell cycle was arrested at G1/G0 phase, and the results of transwell assays revealed that the cell invasion and migration abilities were suppressed in experimental group compared with those in control group. According to the results of Western blotting, after interfering with the expression of DDX11-AS1 in BC cells, there were changes in the expressions of molecular markers for EMT. In BC, the expression of lncRNA DDX11-AS1 is up-regulated, which promotes the proliferation, migration and invasion of BC cells by regulating EMT.